2021
DOI: 10.22146/jsds.1020
|View full text |Cite
|
Sign up to set email alerts
|

Kampung Tangguh: Wujud Kolaborasi antar-Stakeholder dalam Merespons Pandemi COVID-19

Abstract: Kolaborasi dalam penanganan pandemi COVID-19 sangat dibutuhkan, terutama dalam menangani permasalahan-permasalahan yang muncul. Penelitian ini mencoba untuk menemukan bentuk kolaborasi antar aktor dalam Program Kampung Tangguh. Selain itu, penelitian ini bertujuan untuk mengelaborasiakan peran antar stakeholder dalam merespons pandemi COVID-19, melihat konteks Program Kampung Tangguh Semeru. Menggunakan teori kebencanaan dan konsep terkait desa, penelitian ini berargumen bahwa kunci kesuksesan berjalannya Prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 4 publications
0
9
0
6
Order By: Relevance
“…Second, Probolinggo City. Research conducted by Rahmawati, et al (2021) found that the Tangguh Semeru Benteng Village Program in the Mayangan Village/Subdistrict of Probolinggo City became the Responsibility Village Program in East Java (Susilo, 2020) in Rahmawati, et al (2021) found actors who played a role and collaborating are: local government, academics (Universities) and the community. The government's role is to implement a new life (new normal) and provide facilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, Probolinggo City. Research conducted by Rahmawati, et al (2021) found that the Tangguh Semeru Benteng Village Program in the Mayangan Village/Subdistrict of Probolinggo City became the Responsibility Village Program in East Java (Susilo, 2020) in Rahmawati, et al (2021) found actors who played a role and collaborating are: local government, academics (Universities) and the community. The government's role is to implement a new life (new normal) and provide facilities.…”
Section: Resultsmentioning
confidence: 99%
“…In the city of Probolinggo, the inhibiting factor in handling the spread of Covid-19 is the low public awareness of the importance of preventing Covid-19 (Rahmawati, et al, 2021). Meanwhile, the obstacles faced by the Padang City Government are the low public awareness of the dangers of Covid-19 and their low compliance with existing regulations (Putera, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Meskipun awalnya adalah masalah kesehatan, dampak COVID-19 telah merubah segala tatanan sosial, dan bisa dikatakan sebagai bencana sosial. Munculnya pandemi COVID-19 pemerintah dituntut untuk bergerak lebih cepat dan memberikan tindakan nyata yang diharapkan masyarakat dapat memberikan solusi dalam menangani ancaman kasus COVID-19 269) yaitu melalui produk hukum turunan yang ada di Indonesia (Rahmawati et al, 2021).…”
Section: Pendahuluanunclassified
“…Even though the context is also during a pandemic, the Penta helix collaboration research conducted by Ishak and Solehah iskak (Ishak & Sholehah, 2021) focuses more on the issue of developing small and micro enterprises in the Wonosari sub-district. Another research that focuses on efforts to overcome COVID-19 conducted by Rahmawati et al (Rahmawati et al, 2021)also has the context of collaboration. However, it only focuses on collaborating the three pillars of good governance, namely the government, the private sector and the community.…”
Section: Proceedings Of the First Australian International Conference...mentioning
confidence: 99%
“…The research concluded that the Tangguh Village program and collaboration between stakeholders increased awareness among the community. So that this pandemic would end soon, people would be more obedient to all rules or appeals given by the government, and most importantly, be able to increase the economic numbers that plummeted due to the existence of the pandemic and after a pandemic (Rahmawati et al, 2021). The uniqueness of this study is when it links the concept of Penta helix collaboration with local wisdom, as seen from the use of the typical Suroboyan dialect in the name of the program to form closer bonds with the community.…”
Section: Proceedings Of the First Australian International Conference...mentioning
confidence: 99%